PEMBUATAN BATERAI JERUK BAGI KELOMPOK ANAK DI BTN PUSKOPAD SENTANI KABUPATEN JAYAPURA - Flinn C Radjabaycolle; Yusuf Bungkang (LPPM Uncen, 2023)
Physics needs to be introduced to children early to generate interest in physics. One way is to do simple experiments using tools that can be found around us. Here the investigation is to make a physical model in the form of a lemon battery. This activity was carried out without a long and detailed explanation of the theory of physics because the target community here were children aged seven to twelve years. The purpose is for children to know that lemons can be used as batteries to turn on LED lights. The benefits of this activity are that it can stimulate children's curiosity and problem-solving skills, help social and emotional development, and improve communicative and cognitive abilities. The results showed that the involved children were active and enjoyed their scientific activities. In addition, they also were able to answer questions appropriately and correctly. It is an indicator of the success of this activity. It has also been proven that children don't have to experiment with expensive, hard-to-find equipment to understand physics.Keywords: lemon battery; electricity; LED; JayapuraKeywords: lemon battery, electricity, LED